The effect of elephants (Loxodonta africana, Blumenbach, 1797) on Xeric Succulent Thicket - Knott, Edward Joseph (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2007)
This study looks at the impact of elephant feeding on the Xeric Succulent Thicket component of Eastern Cape Subtropical Thicket (ECST) in Addo Elephant National Park (AENP). Observations of elephant feeding were carried out and vegetation transects were surveyed for impact of elephant feeding. The results indicated that the Nyati elephants spent the majority of their time grazing (nearly 90%), particularly the cow-young herds, and especially when the herd gathered in larger numbers. Browsing events were concentrated on Acacia karroo (81%) and there was no significant difference between the sexes in their preference for this species. Despite being subjected to most of the browsing, the majority of A. karroo trees were undamaged and the effect of elephants was generally light. It appears unlikely that, three years after re-introduction to Nyati, the elephants have had an effect on community structure of the vegetation. Surveys were conducted on stands of the alien invasive weed prickly pear Opuntia ficus-indica, and it was recorded that elephants in Nyati have had a dramatic effect on prickly pear, utilising all adult plants assessed and destroying 70% of them. This level of destruction in such a short period of time suggests that prickly pear is a highly favoured species. The results from the present study suggest that elephants can play a role in the control of prickly pear. Results are discussed in terms of elephants as both megaherbivores and keystone species, and as agents of intermediate disturbance.
Keywords: Addo Elephant National Park (South Africa); African elephant; Elephants -- South Africa -- Eastern Cape; Elephants -- Nutrition -- South Africa -- Eastern Cape; Elephants -- Ecology -- South Africa -- Eastern Cape; Elephants -- Behavior -- South Africa -- Eastern Cape; Succulent plants -- South Africa -- Eastern Cape; Woody plants -- South Africa -- Eastern Cape